Two-rod-antenna microwave injection system for production of circularly polarized microwaves in cylindrical ECRIS cavities. Issue 1 (1st April 2022) - Philipp, Alexandra; Molodtsova, Maria; Ritter, Erik
Abstract: In the design of Electron Cyclotron Resonance Ion Sources (ECRIS) three topics generally need to be addressed: (i) The feed of a microwave to generate a plasma, (ii) the creation of a magnetic field guiding the charged particles, and (iii) the design of an ion extraction system. In this report, we concentrate on improvements of aspect (i), a new microwave injection system introduced to the Dresden ECRIS 2.45M, a permanent-magnet 2.45 GHz ECRIS, applied, e.g., for the production of proton currents in medical particle therapy. The improvements include the replacement of its one-rod antenna system by two rod antennas on one cross-sectional circle of the cylindrical ECRIS cavity positioned under an angle of 90° towards each other. Feeding two microwave signals with a relative phase shift of 90°, a right-hand circularly polarized wave can be created inside the cavity to efficiently heat the electrons. Basic considerations, simulations, and results from first experiments are presented.